P-cresol, a uremic retention solute, alters the endothelial barrier function in vitro - Cerini, Claire; Dou, Laetitia; Anfosso, Francine; Sabatier, Florence; Moal, Valérie; Glorieux, Griet; De Smet, Rita; Vanholder, Raymond; Dignat-George, Françoise; Sampol, José; Berland, Yvon; Brunet, Philippe (Thrombosis and Haemostasis, 2004)
Patients with chronic renal failure (CRF) exhibit endothelial dysfunction, which may involve uremic retention solutes that accumulate in blood and tissues. In this study, we investigated the in vitro effect of the uremic retention solute p-cresol on the barrier function of endothelial cells (HUVEC). P-cresol was tested at concentrations found in CRF patients, and since p-cresol is protein-bound, experiments were performed with and without physiological concentration of human albumin (4 g/dl).With albumin, we showed that p-cresol caused a strong increase in endothelial permeability after a 24-hour exposure. Concomitant with this increase in endothelial permeability, p-cresol induced a reorganization of the actin cytoskeleton and an alteration of adherens junctions. These molecular events were demonstrated by the decreased staining of cortical actin, associated with the formation of stress fibers across the cell, and by the decreased staining of junctional VE-cadherin. This decrease in junctional VE-cadherin staining was not associated with a reduction of membrane expression. Without albumin, the effects of p-cresol were more pronounced. The specific Rho kinase inhibitor, Y-27632, inhibited the effects of p-cresol, indicating that p-cresol mediates the increase in endothelial permeability in a Rho kinase-dependent way. In conclusion, these results show that p-cresol causes a severe dysfunction of endothelial barrier function in vitro and suggest this uremic retention solute may participate in the endothelium dysfunction observed in CRF patients.
Keywords: P-cresol; endothelial permeability; VE-cadherin; actin; Rho kinase